Marked enhancement in the efficiency of deep ultraviolet light-emitting diodes by using a AlxGa1-xN carrier reservoir layer. (31st May 2019) - He, Longfei; Zhao, Wei; Zhang, Kang; He, Chenguang; Wu, Hualong; Liu, Xiaoyan; Luo, Xingjun; Li, Shuti; Chen, Zhitao
Abstract: The advantages of using an Al x Ga1- x N carrier reservoir layer (CRL) instead of the traditional last quantum barrier for deep-ultraviolet light-emitting diodes (DUV LEDs) were investigated. The results indicate that the internal quantum efficiency is markedly enhanced and the efficiency droop phenomenon is alleviated. These improvements are mainly attributed to the significantly enhanced hole-injection and radiative recombination rate. Additionally, when the Al contents of the CRL gradually decrease to that of the quantum wells, a large number of electrons and holes are reserved in the CRL region and recombined to emit DUV light, leading to marked enhancement of the optical performance.